Our legends and journey stories: Exploring culturally sustaining family engagement in classrooms. Issue 3 (3rd July 2021) - Flores, Tracey T.; Springer, Sandra
ABSTRACT: Humanizing family engagement practices seek to foster the community cultural wealth and funds of knowledge to working with and for immigrant families and communities. In this manuscript we explore asset-based theories for working alongside families and communities in our schools, with a focus on classroom examples for involving parents and families in school learning. We share the ways that teachers and schools can build curriculum and engagement opportunities that are welcoming and expansive.